Surgical Outcome of Generalized Dystonia: A single center study - Gurung, Pritam; Shrestha, Resha; Dahal, Rizu; Jha, Saurav; Dhungel, Raju Raj; Dhamala, Januka; Taira, Takaomi; Pant, Basant (Nepal Journal of Neuroscience, 2025)
Introduction: Dystonia is a movement disorder characterized by involuntary, sustained, and patterned muscle contractions, which cause twisting and repetitive movements. Dystonia includes various types of movement disorders such as cervical, generalized, task specific focal hand dystonia. Several potential stereotactic targets have been suggested for the treatment of dystonia such as GPi and PTT.Materials and methods: All the patients of generalized dystonia who underwent surgical interventions in Annapurna Neurological Institute and Allied Sciences since January 2015 till December 2023 were included in our study. We performed unilateral pallidotomy/ pallidothalamic tractotomy for cervical dystonia and bilateral pallidotomies or unilateral pallidotomy and contralateral pallidothalamic tractotomy for generalized dystonia. We used ZD Fishers frame and the thermal lesioning machine of Cosman Radiofrequency (RF) generator with the lesioning electrode of 0.75 mm internal diameter and  2 mm exposed tip was used.Results: There were altogether 16 cases of generalized dystonia. There was overall 70 percent decrease in the symptoms of dystonia. The mean age was 41.49 years±12 years. The male: female ratio was 3:1. The mean percentage change in BFMDRS was 70 percent (p value